Cardiac hemangioma mimicking a neuroendocrine tumor on 68Ga Dotatate PET/CT. Issue 9 (2nd May 2022) - Shah, Amar; Binkovitz, Larry; Layman, Andrew J.; Bois, Melanie C.; Nguyen, Ba
Abstract: Cardiac hemangioma is a rare, benign primary tumor characterized by endothelial proliferation. While reports of cardiac hemangiomas demonstrating 18 F FDG avidity and other forms of hemangiomas showing 68 Ga Dotatate avidity have been published, we present a rare case of primary cardiac hemangioma demonstrating 68 Ga Dotatate avidity, mimicking a primary neuroendocrine tumor.